Innovative Strategies Toward the Disassembly of the EPS Matrix in Bacterial Biofilms - Pinto, Rita M.; Soares, Filipa A.; Reis, Salette; Nunes, Cláudia; Van Dijck, Patrick (Frontiers in Microbiology, 2020)
Bacterial biofilms represent a major concern at a worldwide level due to the high demand for implantable medical devices and the rising numbers of bacterial resistance. The complex structure of the extracellular polymeric substances (EPS) matrix plays a major role in this phenomenon, since it protects bacteria from antibiotics, avoiding drug penetration at bactericidal concentrations. Besides, this structure promotes bacterial cells to adopt a dormant lifestyle, becoming less susceptible to antibacterial agents. Currently, the available treatment for biofilm-related infections consists in the administration of conventional antibiotics at high doses for a long-term period. However, this treatment lacks efficiency against mature biofilms and for implant-associated biofilms it may be necessary to remove the medical device. Thus, biofilm-related infections represent an economical burden for the healthcare systems. New strategies focusing on the matrix are being highlighted as alternative therapies to eradicate biofilms. Here, we outline reported matrix disruptive agents, nanocarriers, and technologies, such as application of magnetic fields, photodynamic therapy, and ultrasounds, that have been under investigation to disrupt the EPS matrix of clinically relevant bacterial biofilms. In an ideal therapy, a synergistic effect between antibiotics and the explored innovated strategies is aimed to completely eradicate biofilms and avoid antimicrobial resistance phenomena.